2012
DOI: 10.1155/2012/258434
|View full text |Cite
|
Sign up to set email alerts
|

Melastoma malabathricum(L.) Smith Ethnomedicinal Uses, Chemical Constituents, and Pharmacological Properties: A Review

Abstract: Melastoma malabathricum L. (Melastomataceae) is one of the 22 species found in the Southeast Asian region, including Malaysia. Considered as native to tropical and temperate Asia and the Pacific Islands, this commonly found small shrub has gained herbal status in the Malay folklore belief as well as the Indian, Chinese, and Indonesian folk medicines. Ethnopharmacologically, the leaves, shoots, barks, seeds, and roots of M. malabathricum have been used to treat diarrhoea, dysentery, hemorrhoids, cuts and wounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(96 citation statements)
references
References 33 publications
0
73
0
12
Order By: Relevance
“…6 Leaves of Melastoma malabathricum possessed antihypertensive, 25 wound healing activity. 6 It contains some phenolic compound such as quercetin, 6 epicathecin, epicathecin galat, kaempferol 6,26 which is suspected as responsible compound for inhibitor of mamalia arginase 1 also cinnamic acid derivate 27 which can be also responsible for the inhibitory effect on arginase. 28 These compound worked synergistically in the extract and showed higher arginase inhibitory effect on arginase than other Part extract of the plant.…”
Section: Figure 1: Melastoma Malabathricum Leavesmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Leaves of Melastoma malabathricum possessed antihypertensive, 25 wound healing activity. 6 It contains some phenolic compound such as quercetin, 6 epicathecin, epicathecin galat, kaempferol 6,26 which is suspected as responsible compound for inhibitor of mamalia arginase 1 also cinnamic acid derivate 27 which can be also responsible for the inhibitory effect on arginase. 28 These compound worked synergistically in the extract and showed higher arginase inhibitory effect on arginase than other Part extract of the plant.…”
Section: Figure 1: Melastoma Malabathricum Leavesmentioning
confidence: 99%
“…Previous study showed that phenolic compounds such as quercetin, kaempferol, epicatechin has inhibitory effect on bovine arginase with IC 50 31.2, 179.1, and 19.9 µg/ml. 1 Melastoma malabathricum containing those three phenolic compounds 6 and other phenolic compounds so we hypothesized that extracts from different plant of this plant may have arginase inhibitory effects. The plant were also chosen based on their pharmacological effect on patogenesis some diseases related to upregulation of arginase such as hypertension, 7-8 hyperlipidemia 9 and wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…Tumbuhan ini banyak digunakan oleh masyarakat sebagai obat untuk mengobati berbagai jenis penyakit, diantaranya pengobatan disentri, diare, luka dan infeksi karena bakteri. Metabolit sekunder yang terkandung dalam ekstrak etanol daun karamunting antara lain flavonoid, saponin, tanin, glikosida, steroid dan triterpenoid [1] . Ilmu pengetahuan dan teknologi yang sangat berkembang pesat membuat daun karamunting dapat digunakan sebagai bahan baku dalam industri farmasi.…”
Section: Pendahuluanunclassified
“…Untuk mengetahui aktivitas ekstrak dalam sediaan sabun cair maka aktivitas antibakteri dari F 2 dikurangi dengan aktivitas antibakteri dari F 1 …”
Section: Hasil Dan Pembahasanunclassified
“…In Southeast Asia, the Melastoma genus encompasses 22 species, 2 subspecies and 3 varieties (Rajenderan 2010;Joffry et al 2012). Melastoma decemfidum is known as the straits rhododendron or locally as 'Senduduk Putih' and thrives in waste grounds and open fields (Khatijah & Noraini 2007).…”
Section: Introductionmentioning
confidence: 99%